The Drift: Care and Repair in Contemporary Lebanon. Issue 1 (2nd January 2018) - Brennan, Maeve
Abstract: This article consists of an introductory text and visual essay based on The Drift, a fifty-one-minute film produced by Maeve Brennan in 2017. The Drift traces the shifting economies of objects in contemporary Lebanon. The film follows three main characters: the gatekeeper of the Roman temples of Niha in the Beqaa Valley; a young mechanic from Britel, a village known for trading automobile parts; and an archaeological conservator working at the American University of Beirut. Set amongst Lebanon's densely layered archaeological and urban sites, it focuses on the desire to reassemble and rebuild, conjuring an image of masculinity and care in a landscape often associated with conflict. These multiple perspectives offer a complex alternative to reductive media representations, providing us with a 'thicker' description.